(untitled) (مجلة إحالات, 2025)
الملخص: تهدفُ هذه الورقة البحثية إلى تحديد أثر التّصورات التّعليميّة على مختلف الأنشطة اللغوية انطلاقا من فهم المكتوب وفهم المنطوق وصولا للتصورات الصّورية وهذا من خلال دراستنا لها في شكل بنائي يحدد أثر الفهم النّاجح والفعال ودوره في عملية إكساب المعرفة للمتعلم الّتي تفترض على المعلم التّقيد بجملة من المعطيات ولعل أهمها على الإطلاق ربط المعارف السابقة باللاحقة، وحسن اختيار المضامين، ومهارة الإقناع إضافة إلى حضور عوامل ذات صلة بالمتعلم أيضًا كالقدرة على الملاحظة وحضور مهارة والاستماع وغيرها من الجوانب الحسية التي تساهم في تفعيل الممارسة الدّيداكتيكية و هو ما سنسعى لتحديده تبعا من خلال ضبط مختلف المفاهيم المتعلقة بالموضوع كمرحلة أولى من خلال دراستها سيكولوجيا وتعليميا ثم توضيح أثر الفهم التصوري والبنائي للتعلمات على عملية إكساب المعرفة للمتعلم كمرحلة ثانية. الكلمات المفتاحية: التّصور؛ المفهوم؛ التّعلمات؛ إكساب المعرفة. The effect of conceptual and constructive understanding of learning in the process of acquiring knowledge to the learner. :Summary this research paper aims to determine the impact of educational perceptions in various fields, starting with an understanding of the written and understandable operative and mere visualizations in a constructive form that determines the effect of successful and effective understanding and its role in the process of acquiring knowledge for the learner that is supposed to be adhered to on the other hand by following a set of data to achieve this Perhaps the most important of them is the linking of previous knowledge with the suffix, good choice of the participants and the skill of persuasion, in addition to the presence of factors related to the learner, such as ability; n observation, skill, listening and other sensory aspects that contribute to the activation of the deductive practice, which we will seek to challenge in terms of it by controlling various concepts related to the subject through studying psychology and education, then clarifying the effect of perception and constructive understanding of the .learning on the process of acquiring knowledge to the learner .